1982
DOI: 10.1073/pnas.79.9.2898
|View full text |Cite
|
Sign up to set email alerts
|

F-actin in conifer roots

Abstract: The distribution of F-actin in the complex tissues of a higher plant organ has been visualized by fluorescence labeling the roots of the conifers Chamaecyparis obtusa and Pseu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Epidermal, cortical, and vascular cells in the elongation zone were characterized by thick, predominantly longitudinally oriented MFs. This organization was similar to the organization of MFs in elongating cells of several vascular plants (Parthasarathy et al, 1985) and vascular tissues of gymnosperm (Pesacreta et al, 1982) and maize roots (Vaughan and Vaughn, 1987). Other studies, however, have reported the occurrence of fine, more or less parallel cortical MFs in elongating tobacco protoplasts (Hasezawa et al, 1989), in carrot (Traas et al, 1987) and alfalfa suspension cells (Seagull et al, 1987), as well as in elongating cells of pea roots (Hush and Overall, 1992).…”
Section: Discussionmentioning
confidence: 80%
“…Epidermal, cortical, and vascular cells in the elongation zone were characterized by thick, predominantly longitudinally oriented MFs. This organization was similar to the organization of MFs in elongating cells of several vascular plants (Parthasarathy et al, 1985) and vascular tissues of gymnosperm (Pesacreta et al, 1982) and maize roots (Vaughan and Vaughn, 1987). Other studies, however, have reported the occurrence of fine, more or less parallel cortical MFs in elongating tobacco protoplasts (Hasezawa et al, 1989), in carrot (Traas et al, 1987) and alfalfa suspension cells (Seagull et al, 1987), as well as in elongating cells of pea roots (Hush and Overall, 1992).…”
Section: Discussionmentioning
confidence: 80%
“…The typical methods for purifying actins from animals and protists such as cycle of Accepted March 13. I990 plants [Taylor, 19811. In many epidermal cells and some elongated vascular parenchyma cells actin is involved in vigorous cytoplasmic streaming [Clayton and Lloyd, 1985;Parthasarathy and Muhlethaler 1972;Pesacreta et al, 1982;Pesacreta and Parthasarathy, 19841. However, nearby cortical cells do not exibit detectable cytoplasmic streaming and a role for actin in these cells is not well established.…”
mentioning
confidence: 99%
“…Such proteins have been isolated from sources as diverse as Physarum [8], Dictyostelium [9], rabbit macrophages [10], human platelets [11], chicken intestinal epithelial cells [12], and brain [13]. In most cases the polymerizability of actin in the crude fraction has been attributed to the coexistence of some specific actin binding proteins [5-71 . Actin has been partially characterized from several plant sources like Tomato [2], Soybean [14], Wheat [15], Conifer root [16], Mung bean [3] and Mimosa pudica [4]. Different forms of cytoplasmic structures like cortical fibers [17], complex dynamic fibers in cultured cells [18], filament meshworks [19], contractile rings during cytokinesis [20] have also been reported.…”
Section: Introductionmentioning
confidence: 99%